2019
DOI: 10.3390/f10040308
|View full text |Cite
|
Sign up to set email alerts
|

Recent Deforestation Pattern Changes (2000–2017) in the Central Carpathians: A Gray-Level Co-Occurrence Matrix and Fractal Analysis Approach

Abstract: The paper explores the distribution of tree cover and deforested areas in the Central Carpathians in the central-east part of Romania, in the context of the anthropogenic forest disturbances and sustainable forest management. The study aims to evaluate the spatiotemporal changes in deforested areas due to human pressure in the Carpathian Mountains, a sensitive biodiverse European ecosystem. We used an analysis of satellite imagery with Landsat-7 Enhanced Thematic Mapper Plus (Landsat-7 ETM+) from the Universit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…This is the first time that Pyramid Dimension and Cube Counting are analyzed for the study of forests. GLCM has also been used in the analysis of forests in the Central Group of Eastern Carpathians in Romania [46]. Compared to the previous study, our results showed that the degree of forest and deforestation disorder in the Curvature Carpathians is higher than that of the Central Group.…”
Section: Discussioncontrasting
confidence: 55%
“…This is the first time that Pyramid Dimension and Cube Counting are analyzed for the study of forests. GLCM has also been used in the analysis of forests in the Central Group of Eastern Carpathians in Romania [46]. Compared to the previous study, our results showed that the degree of forest and deforestation disorder in the Curvature Carpathians is higher than that of the Central Group.…”
Section: Discussioncontrasting
confidence: 55%
“…Complete and updated national scale cartography of harvesting practices is currently missing, as it is not produced for the study area nor at a national scale [15,79]. Besides, the results obtained can be used in the future to develop and adapt forestry management policies to ensure sustainable management of exploited forest areas [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics in the regional profile require detailed research regarding the impact on the other components of the territorial systems that have these economic sectors. Research on quantifying the multiplication effects of drug trade on the local economy can be analyzed with a series of algorithms, which have resulted in correlative analyzes of the relationships between the components of a territorial system [14], [15], [16], [17], [18], [19], [20].…”
Section: Discussionmentioning
confidence: 99%